Effect of doping on Al2O3/GaN MOS capacitance. (August 2022) - Rrustemi, B.; Piotrowicz, C.; Jaud, M-A.; Triozon, F.; Vandendaele, W.; Mohamad, B.; Gwoziecki, R.; Ghibaudo, G.
Highlights: Al2 O3 /GaN MOS capacitance measurements with n-doped GaN, NID-GaN and p-GaN have been analysed with 1D Schödinger-Poisson simulations. Quantum capacitance better matches experimental data. N A - - N D + is extracted in p-GaN using 1/C2 vs VG method. In Al2 O3 /p-GaN case, the negative charge induced by p-doping is most likely compensated by positive charges at the oxide level, which prevents the increase of VTH . Abstract: This paper investigates the turning-on-voltage (VFB /VTH ) of Al2 O3 /GaN MOS stacks with n-doped GaN, p-doped GaN and not intentionally doped (NID) GaN by exploiting capacitance measurements on large gate area test structures with systematic variation of Al2 O3 thickness (tox ). Measurements are compared with 1D Schrödinger-Poisson simulations including incomplete ionization model. The necessity of using a quantum description of electron density is demonstrated especially for thinner gate oxides. We found that, contrary to what is expected, p-doping below the channel barely increases the VTH and the VTH is independent of tox, even if the density of activated acceptors is demonstrated to be sufficiently high. Our results highly suggest that the negative charge induced by p-doping is compensated at the oxide level.